Utilization Augmented Reality Technology on Purchase Products in E-commerce - Muhamad Adam Andhika; Nesta Muhammad Akbar M; Maulvi Muhammad Faruqi (International Journal of Research and Applied Technology (INJURATECH), 2023)
E-commerce or known with e-commerce is trading electronic, easy e-commerce is online catalo from traded products. Survey we are social conducted in April 2021 shows that as many as 88.1% of internet users in Indonesia use service e-commerce for buy product certain, one of is furniture products. Destination from study this is designing an application Android mobile based that works for educate Public about application technology Augmented Reality on purchase furniture products in e-commerce, methods on research this is descriptive analyst with approach qualitative. Whereas The method in Augmented Reality is multimarket, where user can scan markers _ together for showing virtual object to real world by real-time. Development application this could give description new to user e-commerce that will buy furniture products, users could see product in 3d and get more information _ useful compared with information through picture or description from furniture products, applications this aim for educate public that Augmented Reality is a technology that will Becomes solution new for face all challenge on purchasing furniture products in e-commerce.